2018
DOI: 10.3390/molecules23040802
|View full text |Cite
|
Sign up to set email alerts
|

Expression Stabilities of Ten Candidate Reference Genes for RT-qPCR in Zanthoxylum bungeanum Maxim

Abstract: Real-time reverse transcription quantitative PCR has become a common method for studying gene expression, however, the optimal selection of stable reference genes is a prerequisite for obtaining accurate quantification of transcript abundance. Suitable reference genes for RT-qPCR have not yet been identified for Chinese prickly ash (Zanthoxylum bungeanum Maxim.). Chinese prickly ash is the source of an important food seasoning in China. In recent years, Chinese prickly ash has also been developed as a medicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…The reliability of RT-qPCR data is affected by the reference gene and sample preparation [4]. Their expression shows large variations in different tissues, developmental stages, and under different stresses [8][9][10][11]. However, an increasing number of studies have shown that none of the common reference genes meet this criterion for all of the test conditions.…”
mentioning
confidence: 99%
“…The reliability of RT-qPCR data is affected by the reference gene and sample preparation [4]. Their expression shows large variations in different tissues, developmental stages, and under different stresses [8][9][10][11]. However, an increasing number of studies have shown that none of the common reference genes meet this criterion for all of the test conditions.…”
mentioning
confidence: 99%
“…The qRT-PCR assays were carried out on a CFX96 Real-Time PCR Detection System (Bio-Rad, Hercules, CA, USA). The reaction system was of 10 μl, containing 5 μl of 2× SYBR Premix Ex Taq II (TaKaRa), 1 μl of cDNA, 1 μl of each of the upstream and downstream primers and 2 μl of ddH 2 O. ZbUBQ and Zbα-EF were used for the reference genes to correct the RT-qPCR data (Fei et al, 2018). The RT-qPCT reaction system of miRNAs is identical to mRNA, with a reaction system of 10 μL, containing 5 μL of 2× SYBR Premix Ex Taq II (TaKaRa, Beijing, China), 1 μL of cDNA, 1 μL of each of the forward and universal reverse primer and 2 μL of ddH 2 O. U6 was used for the correction of relative expression levels of miRNAs (Zhang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was performed in a Bio-Rad CFX96™ system (Bio-Rad, America) with SYBR Premix Ex Taq™ II (TaKaRa, Japan). ZaUBQ was selected as an internal control according to a previous study [2]. The 2 -ΔΔCt method was used to calculate the relative expression levels of the genes in different samples [63].…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%
“…Zanthoxylum armatum (Rutaceae), commonly known as green Sichuan pepper, is one of the most economically important trees in Sichuan Province and is widely distributed in most parts of southwest China and some parts of southeast Asia [1]. The production of Z. armatum is currently a billions of dollars commercially, and this species has a long history of cultivation in China because it is one of the eight main spices used in Chinese cuisine and is an essential ingredient in Sichuan hot-pot, with a special numbing taste [2]. However, the underlying regulatory mechanism of the genes associated with the numbing taste remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%